Abdominal tuberculosis: an epidemiological profile and management of 40 cases in a tertiary set up - Urabinahatti, Kiran Arjun; Singh, Atul Kumar; Nayak, Ashok; Gupta, Rachna; Jain, Mayank; Dubey, Chandrashekar; Garg, Rishi Kumar (International Surgery Journal, 2016)
Background:Tuberculosis is the most important communicable disease world-wide. It is an important cause of morbidity in India. Abdominal tuberculosis mimicks most abdominal diseases and hence is a difficult diagnosis. This study aims to document the epidemiological profile and management strategies of abdominal tuberculosis according to various sites and surgical pathology. Methods: Forty new cases of abdominal tuberculosis were diagnosed and treated over a period of one year (2014-2015) in surgical wards of Shyam Shah Medical College and associated Sanjay Gandhi Memorial Hospital, Rewa (M.P). The patients were selected after they were diagnosed as abdominal tuberculosis on the basis of clinical history, thorough clinical examination and clinical picture during surgery. Further diagnosis was confirmed by histopathology and tissue culture studies. All the patients diagnosed with abdominal tuberculosis, were put on ATT for a period of 6 month, and they were asked to present themselves for follow up at regular intervals. Results:Out of 40 patients with abdominal tuberculosis, 26 were males (65%) and 14 (35%) were females. male to female ratio was 1.8:1. Adults in their 3rd decade (37.5%) and 4th decade (22.5%) were most commonly affected. Pain abdomen was the most common presenting complaint present in 82.5% cases. Abdomen distension was the most common sign (75%). Pulmonary tuberculosis was associated with in 22.5% cases. 5% cases of abdominal tuberculosis were co infected with HIV infection. 55% cases underwent surgical management followed by ATT, and 45% cases needed only ATT as treatment. In cases explored surgically, ulcero sclerotic type (ileal stricture with perforation) was the most common pathology seen in 31.8% cases. Ileocecal region was the most common site of involvement with 67.3% occurrence. Mortality rate was 5%. Conclusions:Abdominal tuberculosis is predominantly seen in low socio economic group. Adults in their 3rd and 4th decades are most commonly affected, which is the earning age group and hence can have economic implications. Majority of cases were of primary intestinal type and in some it was secondary to pulmonary tuberculosis. Majority of cases underwent surgical management followed by ATT. Anti tuberculosis therapy is still the treatment of choice in abdominal tuberculosis and surgery is only indicated in various complication of abdominal tuberculosis.